Pengaruh Citra Merek dan Penggunaan Instagram @Medantalk terhadap Pemenuhan Kebutuhan Informasi Followers - Fauzi Akbar; Rahmanita Ginting (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
Instagram is a social media platform to access the latest information needs. The use of Instagram social media by some people is sometimes more than the use of print media. The @medantalk Instagram account is an account that often presents content from news of crime, fires, natural disasters, accidents, trending events discussed in Medan City. The purpose of this study was to determine how much influence the brand image and the use of social media Instagram together have on fulfilling the information needs of @medantalk followers. This research was conducted on social media Instagram @medantalk with a total sample of 204 followers of the @medantalk Instagram account who live in Medan and its surroundings. Data were collected using a questionnaire. The data analysis used is multiple linear regression test using SPSS for Windows version 24.0. The result of multiple linear regression analysis shows that the variable that most influences the followers 'information needs variable (Y) is the brand image variable (X1) is positive, so it can be said that the higher the brand image variable, the higher the followers' information needs. while the variable use of Instagram (X2) has a positive effect, so it can be said that the higher the variable use of Instagram, the higher the information needs of followers. Thus it can be said that the brand image (X1) and the use of Instagram (X2) together have a positive effect on information needs (Y).